Case Report: Epistaxis with electroconvulsive therapy: a report of 2 patients - Yang, Xin; Fang, Shuping; Liu, Yang; Li, Jin; Kuang, Weihong (Frontiers in Psychiatry, 2025)
Electroconvulsive therapy (ECT) is an effective treatment for various psychiatric disorders such as depression, bipolar disorder, and schizophrenia but is associated with certain side effects. Epistaxis following ECT appeared to be rare, with few reports in the medical literature. We reported two cases of epistaxis following ECT. In one case, we observed a sudden transient increase in blood pressure during ECT, followed by epistaxis. In the other case, the patient developed epistaxis after ECT, with subsequent ECT sessions leading to increasingly difficult-to-control nosebleeds. Nasal endoscopy revealed vascular engorgement in the Little’s area. Our cases suggested that sudden increases in blood pressure during ECT may trigger epistaxis. Repeated ECT sessions may exacerbate this issue, making epistaxis more challenging to manage. Clinicians must be aware of this potential adverse event and should reevaluate the efficacy and risks of ECT for patients who develop epistaxis.